Lipase‐Triggered Water‐Responsive "Pandora's Box" for Cancer Therapy: Toward Induced Neighboring Effect and Enhanced Drug Penetration. Issue 14 (27th February 2018) - Wang, Cheng; Chen, Shaoqing; Wang, Yunxin; Liu, Xuerong; Hu, Fuqiang; Sun, Jihong; Yuan, Hong
Abstract: Insufficient drug release as well as poor drug penetration are major obstacles for effective nanoparticles (NPs)‐based cancer therapy. Herein, the high aqueous instability of amorphous calcium carbonate (ACC) is employed to construct doxorubicin (DOX) preloaded and monostearin (MS) coated "Pandora's box" (MS/ACC–DOX) NPs for lipase‐triggered water‐responsive drug release in lipase‐overexpressed tumor tissue to induce a neighboring effect and enhance drug penetration. MS as a solid lipid can prevent potential drug leakage of ACC–DOX NPs during the circulatory process, while it can be readily be disintegrated in lipase‐overexpressed SKOV3 cells to expose the ACC–DOX core. The high aqueous instability of ACC will lead to burst release of the encapsulated DOX to induce apoptosis and cytotoxicity to kill the tumor cells. The liberated NPs from the dead or dying cells continue to respond to the ubiquitous aqueous environment to sufficiently release DOX once unpacked, like the "Pandora's box", leading to severe cytotoxicity to neighboring cells (neighboring effect). Moreover, the continuously released free DOX molecules can readily diffused through the tumor extracellular matrix to enhance drug penetration to deep tumor tissue. Both effects contribute to achieve elevated antitumor benefits. Abstract : The high aqueous instability of amorphous calcium carbonate (ACC) is employed to construct doxorubicin (DOX)‐preloaded and monostearin (MS)‐coated "Pandora's box" (MS/ACC–DOX) NPs for lipase‐triggered water‐responsive drug release in lipase‐overexpressed tumor tissue to induce a neighboring effect and enhance drug penetration, which shows elevated antitumor benefits both in vitro and in vivo.